2013
DOI: 10.1080/00319104.2012.682260
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Herráez equation correlating viscosity in binary liquid mixtures exhibiting strictly monotonous distribution

Abstract: Recently, Herra´ez et al. proposed a new correlation equation, which introduces a correcting polynomial as an exponential-acting upon the molar fraction of one of mixture components. This equation is found to be widely applicable with more reasonable accuracy in systems exhibiting monotonous distribution than those presenting an extremum. In previous works, we have found that the first adjustable parameter of this equation is a universal exponent (0.5 or 1) for dioxane-water and isobutyric acid-water mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In the present study the excess molar properties and viscosity deviations [1][2][3][4][5][6][7][8] are fitted to the reduced Redlich-Kister (R-K) equation along with its corresponding relative properties and the Herráez 17,18 and Belda correlative equations [19][20][21] . In addition, the reduced R-K function relative to the viscosity Arrhenius activation energy which is equivalent to the apparent molar property gives more information because it is more sensitive than the excess property to interaction 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the excess molar properties and viscosity deviations [1][2][3][4][5][6][7][8] are fitted to the reduced Redlich-Kister (R-K) equation along with its corresponding relative properties and the Herráez 17,18 and Belda correlative equations [19][20][21] . In addition, the reduced R-K function relative to the viscosity Arrhenius activation energy which is equivalent to the apparent molar property gives more information because it is more sensitive than the excess property to interaction 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…It revealed that the deviations of absolute viscosity determined with the Herráez equation generally lead to reliable results for several studied fluid mixtures showing strictly monotonous variation in dynamic viscosity values with molar fraction, but the model records inferior performance when distribution exhibits an extremum [37,38]. Then, the following expression was proposed:…”
Section: Temperature-dependence Of Liquid Shear Viscositymentioning
confidence: 99%
“…Herráez et al [37,38] suggested correlation empirical equation (eqns. 4 or 7) which introduces a correcting polynomial (eqns.…”
Section: Temperature-dependence Of Liquid Shear Viscositymentioning
confidence: 99%
See 2 more Smart Citations